On some miscellaneous sea cucumbers (Echinodermata: Holothuroidea) in the collections of the South African Museum with three new species - Thandar, Ahmed S. (Zootaxa, 2018)
A miscellaneous collection of mostly small holothuroids, comprising some 140 specimens, received from the Iziko South African Museum (SAM), are here recorded and/or briefly described. Of these, one jar contained a badly mutilated holothuroid which was unidentifiable and hence not included here. The remaining material comprises 18 nominal species and an indeterminate elasipodid, perhaps representing a species of Benthodytes. Of the 18 nominal species, four are new to science, one of which has already been described as Trachythyone flaccida Thandar, 2013. Another, although represented by a single mature specimen from deep-water off the Transkei coast (Eastern Cape Province), is so different from its congeners that it is also described as a new species, Stereoderma mohammedi n. sp. Two other specimens, although juvenile, are so extraordinary in their composition of ossicles, that they are also taken to represent another new species, ?Temparena trouspetita n. sp. The collection also includes a single specimen of Synallactes, which together with a specimen misidentified as S. viridilimus by Thandar (2008), is also described as a new species, S. quatrami n. sp. The remaining species proved to be either new records for the southern African region or already well-known southern African forms whose distribution ranges have now changed.